Adsorption of methylene blue on agroindustrial wastes: Experimental investigation and phenomenological modelling. (January 2019) - Meili, L.; Lins, P.V.S.; Costa, M.T.; Almeida, R.L.; Abud, A.K.S.; Soletti, J.I.; Dotto, G.L.; Tanabe, E.H.; Sellaoui, L.; Carvalho, S.H.V.; Erto, A.
Abstract: In this work, agro-wastes coming from soursop (peel, seeds and pulp fiber) and sugarcane (bagasse) are used as low-cost biosorbents to remove methylene blue (MB) from aqueous media. Batch experiments are performed under different experimental conditions investigating the effects of biosorbent amount, dye concentration and stirring rate. The best results were found using soursop wastes for a MB concentration of 100 mg L −1, using 0.75 g of residue and a stirring rate of 110 rpm, removing a percentage above 90%. Theoretically, adsorption kinetic can be successfully described by the pseudo-second order model. Redlich-Peterson and Sips models are adopted to interpret the equilibrium adsorption of MB on sugarcane bagasse and soursop residue, respectively. Interestingly, the monolayer model with single energy derived by statistical physics theory is also applied for a deeper explanation of the adsorption mechanism of MB on both the adsorbents. The application of this model allows defining the adsorption geometry of the investigated adsorbate and provides important information about the interactions between the adsorbate and sorbents. In particular, the modelling analysis by statistical physics allows defining that the dye molecules are adsorbed in vertical position and the adsorption process is multi-molecular (i.e. n > 1). Finally, the estimation of adsorption energy suggested that MB adsorption on biosorbent is a physisorption process.